Conhecimento dos universitários de instituição pública sobre Papilomavírus Humano (HPV) e sua relação com câncer de cabeça e pescoço e oral - Vieira, Valquiria Kulig Vieira (2022)
The Human Papillomavirus (HPV) is a virus that settles on the skin or mucous and can affect men and women in different age groups. No matter how many studies there are in the basic health networks and the media about HPV, several have shown adverse viruses in the population in this regard. Health information or the absence of it can contribute to the health of the population and consequent risk. The objective was to understand university students’ knowledge on HPV and its relation to head and neck and oral cancers. This is a cross-sectional study which applied an online questionnaire a set divided into two sections of questions was elaborated encompassing socioeconomic aspects, about the virus, related pathologies, risk behaviors, perception of the participants in the form of contagion and preventive measures, such as vaccination to undergraduate students at a public university from a public university in the state of Paraná, Brazil (n=335), between 2020 and 2021. In total, 69.3% of our sample is unaware of the relation between HPV and head and neck cancers and 34.6% claim that HPV fails to cause oral cancer. The participants who knew that HPV could be asymptomatic, cause male genital warts, and were 24 years old or older increased by 9.9 (p=0.029), 4.0 (p=0.015) and 1.9 (p=0.021) times their chance of knowing the viral relation to head and neck cancers. However, students of different health undergraduate courses (OR: 0.419, p=0.002), that have sex at least twice a week (OR: 0.471, p=0.017) and are unaware of the target public for the HPV vaccine (OR: 0.222, p<0.001) are less likely to know about this relation. Students who know the relation between HPV and female (3.6, p=0.010) and male genital warts (3.0, p=0.005) or are immunized (1.8 p = 0.020) are more likely to understand the viral interaction with oral cancer. Those who are unaware of the target public for the vaccine (0.493, p=0.017) also show gaps on their knowledge of this relation. Our findings show that there are limitations on the knowledge about HPV, its vaccine, and its relationship with head and neck and oral cancers. Such conditions can be reversed by awareness campaigns on STIs and the importance of immunization, including in universities.